MODELING AND NUMERICAL SOLUTION OF LIQUID FILTRATION PROCESSES IN MULTILAYER OIL FIELDS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The paper presents the physic and mathematic models for fluid filtration in the multilayered strata with poorly permeable and well permeable layer. Developed computational algorithm and program for the intermediate model. Shows computer experiment compared the results with other modules for the development of a multilayered reservoir field. Based on analysis numerical results is that the approval of the interim model is optimal in terms of efficiency of computer time and memory consumption of computer technology.